Intangible cultural heritage and sociomuseology: study on inventories - Lorena Querol (Cadernos de Sociomuseologia, 2014)
Intangible cultural heritage and sociomuseology: study on inventoriesPhD Thesis in Museology by Maria Lorena Sancho Querol (2012)Advisor: Prof. Doutor Mário Caneva de Magalhães MoutinhoCo-supervisor: Prof. Doutor Luís Sousa Martins This thesis is developed in the field of Sociomuseology, taking as a central axis of reference the concept of Intangible Cultural Heritage defined by UNESCO in 2003: a modern concept in which the material and the intangible are manifested and addressed in an inseparable way.Starting from the Portuguese museological panorama, I carry out a study of the function of the inventory in order to demonstrate the way that, nowadays, it is given a central place in social construction of our cultural heritage and our collective memory.In accordance with this and through a retrospective look, I address the history and evolution of the inventory from the fourteenth century to the present day, describe the experience of the participatory inventory carried out in the context of an international project of cultural development with local communities, and analyze the inventory process, the figure of the inventor and the inventory circuit in 11 Portuguese museums. Finally, I present a theoretical reflection on the role and dimension of participation in the construction of the museological inventory, as a scenario for the democratization of memory. Keywords: Inventory, Museum, Intangible Cultural Heritage, Citizen participation, Patrimonialization, Sociomuseology.